Realising Socio-Economic Rights of Refugees and Asylum Seekers in Africa
XVII, 410 p.
Keywords: This book examines the socio-economic rights challenges of refugees and asylum seekers in Africa. It seeks to fill a major gap in the literature by providing a nuanced discussion of the barriers to the realisation of the socio-economic rights of refugees and asylum seekers in Africa. It equally aims to provide some concrete recommendations to African governments towards the realisation of the socio-economic rights of refugees and asylum seekers. With the aid of lessons from selected African countries, this book highlights the gaps, challenges and good practices regarding the realisation of the socio-economic rights of refugees and asylum seekers in the region. The book will be useful to researchers, students, academicians, policymakers, and international organisations or institutions interested in advancing the rights of refugees and asylum seekers. Ebenezer Durojaye is Professor and Head of the Socio-Economic Rights Project at the Dullah Omar Institute, University of the Western Cape, South Africa. His areas of research include human rights, socio-economic rights, sexual and reproductive health and rights, gender, and constitutionalism. Robert Doya Nanima is Senior Lecturer in the Department of Criminal Justice and Procedures, Faculty of Law, University of the Western Cape, South Africa. He is a member of the African Committee of Experts on the Rights and Welfare of the Child. Abiola Idowu-Ojo is Senior Legal Officer with the African Commission on Human and Peoples’ Rights (ACHPR), Banjul, The Gambia. She has a long experience in human rights research and practice, both within the ACHPR/African Union and as an independent expert. Gladys Mirugi-Mukundi is Researcher with the Socio-Economic Rights Project at the Dullah Omar Institute, University of the Western Cape, South Africa. She has a long experience in research, advocacy and teaching in the field of socio-economic rights.